Reprogramming of hepatic fat accumulation and 'browning' of adipose tissue by the short-chain fatty acid acetate - Sahuri-Arisoylu, M; Brody, L P; Parkinson, J R; Parkes, H; Navaratnam, N; Miller, A D; Thomas, E L; Frost, G; Bell, J D (International Journal of Obesity, 2016)
Background/Objectives: Short-chain fatty acids, produced by microbiome fermentation of carbohydrates, have been linked to a reduction in appetite, body weight and adiposity. However, determining the contribution of central and peripheral mechanisms to these effects has not been possible. Subjects/Methods: C57BL/6 mice fed with either normal or high-fat diet were treated with nanoparticle-delivered acetate, and the effects on metabolism were investigated. Results: In the liver, acetate decreased lipid accumulation and improved hepatic function, as well as increasing mitochondrial efficiency. In white adipose tissue, it inhibited lipolysis and induced 'browning', increasing thermogenic capacity that led to a reduction in body adiposity. Conclusions: This study provides novel insights into the peripheral mechanism of action of acetate, independent of central action, including ‘browning’ and enhancement of hepatic mitochondrial function.